PERLINDUNGAN HUKUM BAGI PENYEWA OBJEK HAK TANGGUNGAN YANG DILELANG DITINJAU DARI UNDANG-UNDANG HAK TANGGUNGAN - Yuliana, Yuliana; Amelia Nur Widyanti,; Yuliana Setiadi, (Journal of Innovation Research and Knowledge, 2025)
Problems that often arise related to objects that are used as collateral for mortgage rights are being burdened with other rights, which means that there is a third party who owns or controls the rights to the object that is used as collateral, and based on this, the third party also has the right to submit or a settlement or legal action against him. The problems studied in this thesis are First, how is the legal strength of a lease agreement over an object encumbered with a mortgage assessed under the Mortgage Law? Second, how is legal protection afforded to the lessee of mortgage property subject to auction as a result of the enforcement of a mortgage right under the provision of the Indonesian Mortgage Law? The theories used in analyzing these problems are the theory of agreement and the theory of legal protection. The method used in this study with the type of normative legal research, namely library legal research or secondary data with primary, secondary and tertiary legal materials sources. The research approach used is the legislative approach, conceptual approach, analytical approach, and case approach and the legal material collection technique is carried out by identifying and inventorying positive legal rules, book literature, journals and other legal sources. For the legal material analysis technique, it is carried out with grammatical and systematic legal interpretation while the legal construction method is with analogy and legal refinement. Base on the results of this research, it can be concluded that the legal strength of a lease agreement over an object of mortgage is relatively weak, as the mortgage holder holds a preferred right in accordance with the provisions of the Indonesian Mortgage Law, unless the lease agreement has been formally registered with the land office. Legal protection for lessees of mortgaged property subject to foreclosure is not expressly accommodated by the Mortgage Law. However, lessees may seek legal remedies against the lessor through a civil lawsuit, in which the creditor may also be included as a co-defendant.